Morphological characterization and genotyping of the marbled crayfish and new evidence on its origin - Vogt, Günter (Zootaxa, 2018)
The obligately parthenogenetic marbled crayfish, Procambarus virginalis, is the first formally described asexual species of the Crustacea Decapoda. It is a triploid descendant of the sexually reproducing slough crayfish, Procambarus fallax. Here we describe the morphology of cultured and wild marbled crayfish of wide size ranges in detail and photodocument all taxonomically relevant characters. Some morphological traits and coloration showed considerable variation within populations despite the monoclonal nature of marbled crayfish. There were also significant differences between wild and laboratory populations with respect to body proportions, coloration and spination. Comparison with Procambarus fallax revealed no qualitative morphological characters that unambiguously identify the marbled crayfish. Analysis of the mitochondrial cytochrome c oxidase subunit I gene (COI) and nuclear microsatellites of marbled crayfish and Procambarus fallax from different sources indicated that the tri-allelic microsatellite PclG-02 is better suitable than COI to identify the marbled crayfish. A respective identification key is provided. The COI and microsatellites of Procambarus fallax from different areas of Florida and southern Georgia suggest that the parents of the first marbled crayfish may have come from northern Union County, northern Florida.
Gesehen am 27.03.2019